The development of mixed-matrix membrane incorporated with reduced graphene oxide synthesized using murraya koenigii leaf for oil/water separation - Mohd Akhair, Siti Hajar (2022)
The incorporation of additives, either from organic or inorganic materials, to form polymeric mixed-matrix membrane (MMM) is one of the most common and favoured techniques to improve membrane properties and performance. In this study, reduced graphene oxide (rGO) with a strong effect of hydrophobicity and oleophilicity was integrated into a polysulfone (PSf) membrane’s structure to study the effect of characteristic and property polymeric of mixed-matrix membrane towards oily water separation process. The formation of rGO via biosynthesis revealed with the appearance matched peak with rGO as well as the peak of oxygen-containing functional groups slowly reduced as shown by thermal analysis results. Further investigation, towards oleophilicity property of rGO also proven the rGO powder has strong attraction towards oil and easily repel water molecule. This was proven by permeate oily-water flux performance that revealed adding of rGO into a PSf membrane has result in higher of oil permeate as compared to other. Characteristic observation also revealed membrane with PSf/rGO has higher contact angle and dense top layer indicating strong hydrophobicity effect that leads to delay demixing mechanism. Thus, incorporating of bio-sythesized rGO powder from curry leaf extract enhanced membrane’s hydrophobicity and oleophilicity properties that provide better attraction towards oil molecules as compared to graphite and GO powder.